2019
DOI: 10.1177/1179069519839990
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Mental Health Facilities and De-addiction Centers in India

Abstract: Not much is known about disease prevalence, treatment outcomes, trained manpower, programs, and patients’ awareness of diseases from South Asia, compared with the Western world. While other aspects are improving, the quantitative evaluation of awareness of diseases is lagging. Compared with other diseases, the situation for mental health disorders and addiction is worse. While no single study can fully quantify all aspects of awareness, a good starting point is to understand if increasing the number of mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Some of the research found in our literature search for these regions captured mental health literacy rather than aspects of stigma leading to the exclusion for these contributions for the current purpose. For example, while we identified 1 study each from India (Singh et al, 2019) and rural China (Yu et al, 2016), their surveys were designed to measure the public's knowledge on mental diseases rather than aspects of stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the research found in our literature search for these regions captured mental health literacy rather than aspects of stigma leading to the exclusion for these contributions for the current purpose. For example, while we identified 1 study each from India (Singh et al, 2019) and rural China (Yu et al, 2016), their surveys were designed to measure the public's knowledge on mental diseases rather than aspects of stigma.…”
Section: Discussionmentioning
confidence: 99%
“…A large survey by Singh et al 11 (p.2) confirms that mental health stigma is a chronic problem in India. The authors recommend ‘community education and training at a grassroots level’ and highlight the success of outreach projects.…”
Section: Introductionmentioning
confidence: 99%